Infrastructure Development Strategy for Housing and Settlement in Sub-District Coastal Of â€œKota Kendalâ€ - Jamilla Kautsary (International Conference on Coastal and Delta Areas, 2015)
Kota Kendal is one of the small citythat lay in the northern coast of java.This city passed by the north coast road connecting Surabaya, Semarang and Jakarta. This area as part of the coastal area, does not separated from environmental problems such as flooding and tidal wave.These conditions have been impact on the quality of infrastructure problems in housing and settlement area.This problem becoming more complicated when spatial planning and development planning have not been integrated in directing the construction of infrastructure.The strategy of housing andsettlementâ€™s infrastructure development in the coastal city of Kendal were expected to give description efforts to solving a problem in the development of infrastructure in coastal urban areas.The author usedresearch method of deductive phenomenology and a participatory planning for examining this problem.This was done to searchactual problems in the field. From a series of observations in the fieldand problem analysis, researchers found various infrastructures problem were: housing facilities that are unsuitable, bad condition of the water system, waste water and sanitation, drainage , wastemanagement and bad environment.In order to solve the problem some strategy that can be applied between is to build the house of milk , service improvement company and the utilization of the potential of clean water other , infrastructure development waste processing and m publictoiled, normalization of drainage and improve waste management services